Does the Drug Facts Label for nonprescription drugs meet its design objectives? A new procedure for assessing label effectiveness. Issue 2 (July 2017) - Ryan, Michael P; Costello-White, Reagan N
We demonstrate an expanded procedure for assessing drug-label comprehension. Innovations include a pretest of drug preconceptions, verbal ability and label attentiveness measures, a label-scanning task, a free-recall test, category-clustering measures, and preconception-change scores. In total, 55 female and 39 male undergraduates read a facsimile Drug Facts Label for aspirin, a Cohesive-Prose Label, or a Scrambled-Prose Label. The Drug Facts Label outperformed the Scrambled-Prose Label, but not the Cohesive-Prose Label, in scanning effectiveness. The Drug Facts Label was no better than the Cohesive-Prose Label or the Scrambled-Prose Label in promoting attentiveness, recall and organization of drug facts, or misconception refutation. Discussion focuses on the need for refutational labels based on a sequence-of-events text schema.